Economic Policies to Achieve Food Security in the kingdom of Saudi Arabia During the Period (1990- 2017) "wheat as a model" - Almuhanna, Ahmed Saud (Journal of Economic, Administrative and Legal Sciences, 2019)
Due to the obstacles faced by the agricultural sector in the Kingdom of Saudi Arabia, especially, water scarcity, and the state’s adoption of policies to lessen water consumption which led to the shrinking of the total of cultivated areas, especially wheat, and the state’s transition from a self- sufficient wheat producer to an importing state. So the import of these foods is highly affected by the external factors and the global food market. The importance of this study comes from the need to discuss food security policies, especially with the lack of studies on food security in Saudi Arabia. While most of the studies focused on the water security aspect, of which they warned of a possible depletion of groundwater if local agriculture continues. This study aims to identify the policies adopted by the Kingdom to achieve food security in general, as well as to study the potential l economic factors affecting the supply of wheat commodity in particular in its capacity as one of the most important strategic commodities. The study hypothesizes that there is a relationship between the level of food security of wheat and a number of economic variables. The study used the descriptive approach in explaining the concept of food security, its aspects, problems and policies to achieve it. It also relied on the standard approach to test the study hypotheses. The most important results are: there is a relationship between food security in the Kingdom and a number of economic variables; the most important of which is the level of per capita income, as its increase leads to the increase of indivduals capacity to afford import costs of basic commodities like wheat, and the increase of food supplies available for consumption as well as international food prices have impact of the flow of these supplies. The main recommendations of the study: Commitment to national initiatives to face the challenges and implementation of national transformation programs that aim to achieve sustainable development, the most important components of which are: achieving sustainable economic growth and protection of the environment and natural resources and the adoption of appropriate agricultural strategies.